Implication of common housekeeping in the phylogenetic development of monkeypox - Santamaría Veliz, Olivia (2022)
Monkeypox is a reemerging zoonosis caused by the monkeypox virus (MPXV), which belongs to the poxviridae family, to the orthopoxvirus genus. It was first identified in 1958, since then there have been outbreaks in different countries of the African continent. However, it is verified that the pathogen has evolved, due to the presence of genomic polymorphism, loss of genes, etc. Until reaching clade IIb, which has caused the outbreak in 2022. Among the factors that have influenced its phylogenetics, the following have been identified: biogeographical barriers, drastic climatic variations and human actions. The latter depend on the relationship of the person with their natural environment, among them are: the destruction of forest areas, consumption of wild animals and the trafficking of species. These activities, in addition to violating the rights of the person such as a healthy environment, equitable distribution of natural resources and social welfare, provide the necessary conditions for viruses of different species to be transmitted to the person and generate zoonoses that can put public health at risk. For this reason, it is essential to care for the common home to prevent the spread of zoonotic diseases such as monkeypox.